Giving the influenza jab: a review of the law - Richard Griffith (British Journal of Community Nursing, 2004)
District nursing sister June Harris recently completed the administration of 30 ‘flu jabs to frail older residents of a local care home. June encountered a number of problems when administering the vaccinations. Relatives of five residents with advanced dementia did not want them to have the injection, mainly because they had heard that it would give the recipient the ‘flu. An 85-year-old resident has complained that while she agreed to have a ‘flu jab it now appears she also had a pnumococcal vaccination as well that no one told her about. More seriously, June has recently heard that one resident is in hospital having contracted Guillian-Barré Syndrome as a result of the vaccination. June remembers that this reluctant resident specifically asked if the ‘flu jab would leave her paralysed and June had laughingly replied that she had not paralysed anyone to date. The residents and their families are now threatening legal action.